Rapports paléo-babyloniens d’haruspices - Nougayrol, Jean
treats YOS X 19; Szlechter, TJA pl 24 and 28; AO 7607. Treatment and copies of AO 7615; BM 12287; BM 78564; BM 78655; BM 81364; LB 1835; MAH 16274; Mari A. 860; Mari A. 1081; Mari A. 4222; publ. 1969.